Prospects & challenges of sustainable procurement in Bangladesh Hi-Tech Park Authority - Hasan, Rokibul (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.